379 Consenting on the Day of Surgery – Futility or Formality?. (28th February 2022) - Martyn, C.J.; McGowan, K.E.; Clements, J.M.; Kirk, S.
Abstract: Aim: Obtaining written informed consent is essential prior to proceeding with any surgical intervention. There is no consensus on the timing of when consent is complete. We aimed to assess the consent practices in our institution. Method: A prospective snapshot audit was conducted on consecutive elective general surgical patients over a 4-week Period (August 2021). Data was collected on the content of pre-operative consent discussions as well as when the consent form was completed. Local audit approval was obtained Results: 56 patients underwent an elective general surgical procedure. Median age was 55. 73% (n = 41) were female. 63% cases were for malignant disease (n = 35). All patients completed a consent form 1. 54 patients had documented pre-operative consultations with a consultant. In all malignant cases, patients underwent discussion with a cancer specialist nurse present. All patients received a diagnosis and discussion regarding treatment. 69% of patients underwent discussion about alternative treatment options and a discussion about surgical risk took place in 30% of cases. 95% of patients signed their consent form on the day of surgery with 80% registrars and 20% consultants countersigning the forms respectively. Conclusions: Despite the majority of patient completing their consent form on the day of surgery, the preceding consent discussions would suggest that consent is a process, and that completion of the form is a formality.